Studying the Effects of Roads Geometry and Design Parameters on the Pavement Drainage System - Mohammad Awwad (Civil Engineering Journal, 2021)
Background: Water floods have a considerable impact on roads sustainability by creating roads cracks, breaking down and holes, and failure for some other parts. The existence of good drainage system serviced the road and draining the water resulted from rain floods is crucial. These significant influences can be classified as positive or negative, low, moderate, or high. Aim and Objectives: This paper discusses the water floods and rainfall effects on roads and highways in Jordan as well as the drainage system on road sustainability and performance. The main aim of this paper is to investigate and analyse water as rainfall or floods affecting roads and highways in Jordan. The importance of this study is represented by studying and analysing the effects of rainfall and water floods on road construction and sustainability in Jordan after the latest high rain sizes of this winter and water floods, which affect the roads and highways in a good percentage. The other importance of the study is represented in offering solutions to problems caused by the environmental effects, specially floods and high rainfall rates. Methodology: all data and information about status of Jordanian roads during winter and floods are collected from real cases of about 40 main and semi-main roads in Jordan.  Results and Conclusions: A good drainage system and repair operations and maintenance generally have a positive impact on road sustainability and survival age. The effects of slopes of the road and surface of the asphalt, rainfall intensity, and water flow velocity on drainage length and drainage time and water depth are discussed here. Doi: 10.28991/cej-2021-03091636 Full Text: PDF